Public Relations Role in Combating Corruption in the Kurdistan Region: Field research-study - Hoshiar Muzaffar Ali; Najmadin Hassan Mustafa (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
This is a descriptive field study that the researcher uses exact statistical methods of planimetry in the aim of collecting the real and detailed data and information. The main objective of this research is to analyze the public relations and the improvement in public relations regarding the mechanisms, agenda, strategy, and theories that are needed to build public opinions for the benefit of the society. This study was conducted among public relation employees that work in all the offices and affairs under the mandate of the Public Relation Department in the Kurdistan Regional Government (KRG). The qurestionnnaires were distributed among (108) employees on August 1, 2020. The data was collected on September 1, 2020. The significant methods of the data collection were interviews, written notes, and survey. The survey was separated into 24 questions. Also, the resercher uses the SPSS program application for analyzing statistical data and demonistrating the outcomes. However, the most important outcomes of this research are that the public relations has a significant role in creating the public opinions. In addition, the public relations has its own strategy and mechanism for the important and popular cases in the community, and this has been based on the research results and almost 75.56% of the research participants was agreed with the motion. Furthermore, the public opinion has been taken into consideration form the perspective of the community as well as the Kurdistan Regional Government (KRG) institutions. The public opinion is also represents the majory of the community members as this confirmed by the majority of the research participants (83.33%). The research findings present some recommendations that the public relations (PR) in the the government institutions should be independent. That is, the public relations should not be linked to any other departments and/or entities. In addition, the research also recommends that the public relations should be studied as an independent study program in educational institutions and the universities.